Soil macroarthropod communities of Amazon degraded pastures restore differently during their natural regrowth - Daniel Castro; Clara P. Peña-Venegas; Carlos H. Rodríguez-León; Ervin H. Duran-Bautista; Armando Sterling (Nature Conservation)
Understanding the recovery of soil macroarthropod communities during natural regrowth is crucial to demonstrate complete soil restoration. This is because these organisms can play a key role in shaping soil structure and community dynamics, making them essential to understanding these processes. This study investigates the recovery of soil macroarthropod diversity, density, and biomass across different stages of natural regrowth, focusing on the taxonomic groups and feeding guilds dynamics. Macroarthropod communities were analyzed along a chronosequence (young-age, middle-age, and old-growth) including their vertical distribution (litter, 0–10 cm, 10–20 cm, and 20–30 cm). A total of 20 plots and 100 Tropical Soil Biology and Fertility Programme (TSBF) soil monoliths were sampled. Results revealed an increase in total macroarthropod diversity, biomass, and density with regrowth, but these patterns do not occur in the same way for all macroarthropod groups, emphasizing the complexity of ecological succession. Termites were key ecosystem engineers, shaping community composition at each regrowth stage. Predators and decomposers also exhibited significant changes in response to regrowth, reflecting their sensitivity to ecological disturbances. In contrast, ants and some herbivores showed higher densities and biomass in pastures and early regrowth stages, with notable shifts in species composition over time. Vertical distribution of macroarthropods revealed higher activity at the 0–10 cm depth, with similarities in the composition in litter and 10–20 cm soil depth, highlighting soil microarthropod importance in soil mineralization and humification. These findings underscore the critical role of ecosystem engineers in soil restoration and highlight the need for the conservation of soil biology to enhance soil health.